Markova comfort gay - Portes, Gil M. (Art & Design Culture Q Connection, 2004)
In this exploration of a little-known aspect of World War II in the Philippines, that of homosexual comfort gays, Walter Dempster, Jr., a.k.a Markova, watches a t.v. documentary about comfort women and remembers his own painful story and similar experiences. Sharing the spotlight with his two sons, popular film star Dolphy plays a role entirely stripped of stereotypes, revealing character and strength.